Oral Manifestation of Sexual Transmitted Diseases - Milinia Mongkaren; Aurelia S. R. Supit; Christy N. Mintjelungan; Janno B. B. Bernadus (Universitas Sam Ratulangi, 2022)
Abstract: Sexually transmitted diseases (STDs) are transmitted through sexual contact, and can manifest in the oral cavity. This study aimed to determine the oral manifestations of STDs. This was a literature review study using two databases namely Google scholar and PubMed. The results obtained six cross-sectional studies. Oral manifestations that could occur in patients with STD were necrotizing ulcerative gingivitis, necrotizing ulcerative periodontitis, necrotizing ulcerative stoma-titis, linear gingival erythema, oral candidiasis, sarcoma Kaposi, oral hairy leukoplakia, gonococcal stomatitis, chancre, condyloma acuminata, snail track, and gumma. Oral manifestations caused by bacteria were necrotizing ulcerative gingiva, necrotizing ulcerative periodontitis, necrotizing ulcera-tive stomatitis, gonococcal stomatitis, chancre, snail track, linear gingival erythema, and gumma. Oral manifestation caused by fungi was oral candidiasis and oral manifestations caused by viruses were oral hairy leukoplakia, Kaposi sarcoma, and condyloma acuminata. In conclusion, oral mani-festations of STDs can caused by bacteria, fungi, and viruses. The most common oral manifestation of STDs is oral candidiasis.Keywords: oral manifestations; sexually transmitted diseasesÂ Abstrak: Penyakit menular seksual (PMS) merupakan infeksi yang ditularkan melalui hubungan seksual, yang dapat bermanifestasi pada rongga mulut. Penelitian ini bertujuan untuk mengetahui manifestasi oral PMS. Jenis penelitian ialah suatu literature study. Penelitian ini mempelajari tentang manifestasi oral penyakit menular seksual dengan menggunakan database Google scholar dan PubMed serta tahun publikasi pustaka Februari 2011-September 2022. Hasil penelitian mendapat-kan sebanyak enam pustaka. Manifestasi oral yang terjadi pada pasien akibat infeksi PMS ialah necrotizing ulcerative gingivitis, necrotizing ulcerative periodontitis, necrotizing ulcerative stomatitis, linear gingival erythema, oral candidiasis, sarcoma Kaposi, oral hairy leukoplakia, gonococcal stomatitis, chancre, Condyloma acuminata, snail track, dan gumma. Manifestasi oral yang disebabkan oleh bakteri ialah necrotizing ulcerative gingiva, necrotizing ulcerative periodontitis, necrotizing ulcerative stomatitis, gonococcal stomatitis, chancre, snail track, linear gingiva erythema, dan gumma. Manifestasi oral yang disebabkan oleh jamur ialah oral candidiasis dan manifestasi oral yang disebabkan oleh virus yaitu hairy leukoplakia, sarcoma Kaposi dan condyloma acuminata. Simpulan penelitian ini ialah manifestasi oral PMS dapat disebabkan oleh bakteri, jamur dan virus. Manifestasi oral yang terbanyak ditemui yaitu oral candidiasis.Kata kunci: manifestasi oral; penyakit menular seksual